Liquidity Transformation and Financial Fragility: Evidence from Funds of Hedge Funds - Agarwal, Vikas; Aragon, George O.; Shi, Zhen (Journal of Financial and Quantitative Analysis, 2019)
We examine liquidity transformation by funds of hedge funds (FoFs) by developing a new measure, illiquidity gap, that captures the mismatch between the liquidity of their portfolios and the liquidity available to their investors. We find that higher liquidity transformation is driven by FoFs’ incentives to attract more capital and earn higher compensation. Greater liquidity transformation is associated with higher exposure to investor runs and worse performance during crisis periods. Finally, FoFs mitigate the risks associated with liquidity transformation by maintaining higher cash buffers.